Web and Arduino Automatic Selling Machine Monitoring Prototype - Ritzkal .Ritzkal; Akhmad Abdul Aziz; Fitrah Satrya Fajar Kusumah; Kodarsyah Kodarsyah (Institute of Computer Science (IOCS), 2022)
A vending machine is a type of machine that is very suitable for marketing a product such as automatic sales. These machines also tend to be able to grab more attention in public places. In the beverage machinery industry, there is a lot of competition from large companies, which can make it difficult to market these machines. Many schools and universities already have agreements with companies to place automated beverage machines on site. This tool is designed using the TCS3200 sensor which functions to detect the color of the paper currency to determine the value of the currency. The dc motor functions as an actuator for withdrawing money and the servo motor functions as a container for dropping money every time money comes in. Then the pushbutton and led light function as a drink selection button after the money comes in. The web functions as a provider of information about how many drinks are sold and how many drinks are left in stock, and telegrams serve as a marker/notification when one of the drink's stock runs out. Furthermore, for the drink dropping work system using a dc motor equipped with a spiral in each drink slot. Each money that comes in with a nominal value of Rp. 5,000 or Rp. 10,000 can only make one transaction, because this tool does not accept change. Tests were carried out on currency detection, cash withdrawals, beverage dispensing, web monitoring, and telegram notifications.